HIV Infection, Immunodeficiency, Viral Replication, and the Risk of Cancer - Silverberg, Michael J.; Chao, Chun; Leyden, Wendy A.; Xu, Lanfang; Horberg, Michael A.; Klein, Daniel; Towner, William J.; Dubrow, Robert; Quesenberry, Charles P.; Neugebauer, Romain S.; Abrams, Donald I. (Cancer epidemiology, biomarkers & prevention, 2011)
Background: Few studies have compared cancer risk between HIV-infected individuals and a demographically similar HIV-uninfected internal comparison group, adjusting for cancer risk factors. Methods: We followed 20,775 HIV-infected and 215,158 HIV-uninfected individuals enrolled in Kaiser Permanente (KP) California for incident cancer from 1996 to 2008. Rate ratios (RR) were obtained from Poisson models comparing HIV-infected (overall and stratified by recent CD4 count and HIV RNA) with HIV-uninfected individuals, adjusted for age, sex, race/ethnicity, calendar period, KP region, smoking, alcohol/drug abuse, and overweight/obesity. Results: We observed elevated RRs for Kaposi sarcoma (KS; RR = 199; P < 0.001), non-Hodgkin lymphoma (NHL; RR = 15; P < 0.001), anal cancer (RR = 55; P < 0.001), Hodgkin lymphoma (HL; RR = 19; P < 0.001), melanoma (RR = 1.8; P = 0.001), and liver cancer (RR = 1.8; P = 0.013), a reduced RR for prostate cancer (RR = 0.8; P = 0.012), and no increased risk for oral cavity/pharynx (RR = 1.4; P = 0.14), lung (RR = 1.2; P = 0.15), or colorectal (RR = 0.9; P = 0.34) cancers. Lung and oral cavity/pharynx cancers were elevated for HIV-infected subjects in models adjusted only for demographics. KS, NHL, anal cancer, HL, and colorectal cancer had significant (P < 0.05) trends for increasing RRs with decreasing recent CD4. The RRs for lung and oral cavity/pharynx cancer were significantly elevated with CD4 < 200 cells/μL and for melanoma and liver cancer with CD4 < 500 cells/μL. Only KS and NHL were associated with HIV RNA. Conclusion: Immunodeficiency was positively associated with all cancers examined except prostate cancer among HIV-infected compared with HIV-uninfected individuals, after adjustment for several cancer risk factors. Impact: Earlier antiretroviral therapy initiation to maintain high CD4 levels might reduce the burden of cancer in this population. Cancer Epidemiol Biomarkers Prev; 20(12); 2551–9. ©2011 AACR.